Energy input: The physical essence of electrorheological structural behaviors in waxy crude oil - Hongying Li; Chaoyue Zhang; Jiabao Kang; Yiwei Xie; Qibing Li; Yang Su; Quande Li; Yichen Wei; Jinjun Zhang (Fuel, 2027)

The coupled role of alkali and water in governing the interfacial performance of bilayered metakaolin-based geopolymer-concrete composites: Mechanistic investigations and mix-design regulation - Zheng Chen; Jingwen Tang; Yichen Wang; Tao Su; Chaofan Yi (Applied Clay Science, 2026)

High-accuracy EEG-based driver fatigue detection using feature-coupled tensor decomposition for multimodal brain connectivity analysis - Tian Yan; Hechong Su; Zengyao Yang; Aimin Zhang; Yidan Ma; Xiaolong Wang; Yue Wu; Li Yan; Yichen Wang; Jianfu Cao (Cognitive Neurodynamics, 2026)

Energy-efficient electrochemical ammonia removal enabled by replacing hydrogen evolution with four-electron oxygen reduction at the cathode - Zeyu Du; Yongyang Chen; Xiaowei An; Changhui Zhou; Yaobin Wang; Chaoyue Xie; Ruiqing Zhao; Zhiyuan Su; Zhinan Dai; Yichen Gong; Guanjun Qu; Fangzhou Li; et al. (Water Research, 2026)

Heterogeneous rock abundances in the lunar subsurface revealed by cold-spot craters - Yizhen Ma; Zhiyong Xiao; Yichen Wang; Yiren Chang; Rui Xu; Yan Su (Icarus, 2026)

Sublethal effects of field-recommended glyphosate exposure on the predatory insect Arma chinensis: Growth inhibition and reproductive costs - Zhihan Su; Wenyan Xu; Luyao Fu; Dianyu Liu; Xiaoyu Yan; Yu Chen; Yichen Wang; Chenxi Liu (Environmental Pollution, 2026)

Collaborative optimization pathway of provincial power generation structure in China - Yan Nie; Guoxing Zhang; Yutao Wang; Bin Su; Yichen Feng; Lean Yu (Mitigation and Adaptation Strategies for Global Change, 2026)

Whole-Genome Resequencing Reveals Selection Signals Associated with Vibrio parahaemolyticus Stress Tolerance in Portunus trituberculatus - Dongfang Sun; Hangfeng Pan; Yichen Su; Jiayi Pan; Xianfa Zhou; Baoquan Gao; Jianjian Lv (Marine Biotechnology, 2026)

Synergistic and green decontamination of anion exchange resins: A surfactant and citric acid approach - Yukai Peng; YiChen Wu; Yiduo Du; Ye Tian; Xuebin Su; Rong Hua (Journal of Environmental Chemical Engineering, 2026)

Nano–lignocellulose powder by hydrolysis–oxidation synergism for high strength and adequate barrier bio-composites - Zhikang Su; Yichen Liu; Bing Jiang; Chaohui Yang; Benyou Liu; Maocheng Ji; Yanhui Li; Chuanwei Zhang (Journal of Cleaner Production, 2025)

A preliminary study on the application of scale removal agents in neutral in-situ leaching for unblocking in sandstone-type uranium deposits - Yuxin Chen; Yichen Wu; Yuke Wang; Cong Huang; Xuebin Su; Rong Hua (Journal of Environmental Chemical Engineering, 2025)

Multi-omics analysis reveals an endogenous competitive regulatory mechanism for resistance to Vibrio parahaemolyticus in the swimming crab, Portunus trituberculatus - Dongfang Sun; Xianfa Zhou; Yichen Su; Baoquan Gao; Ping Liu; Jianjian Lv (Fish & Shellfish Immunology, 2025)

The Effect of the Belt and Road Initiative (BRI) on Non-CO2 Agricultural Greenhouse Gas Emission Trends in Southeast Asian Countries - Minpeng Chen; Siqi Li; Xun Su; Yichen Feng; Yichun Peng (Resources, Conservation and Recycling, 2025)

Dynamic variations in flavor profiles of Guizhou high-mountain white tea produced by Eurotium cristatum using solid-state fermentation - Su Xu; Linyao Song; Dajuan Shi; Siyao Wu; Fengwei Ma; Haijiang Chen; Qinglong Meng; Qiang Fei; Lingshuai Meng; Wenneng Wu; Dong Lin; Guangcan Tao; et al. (Food Bioscience, 2025)

Functions of the transcription factor myb-like in sex determination and differentiation in Portunus trituberculatus - Shaoting Jia; Weikang Lan; Yuchao Huang; Yichen Su; Baoquan Gao; Ping Liu; Jianjian Lv (Aquaculture, 2025)

Respiration-Driven Ammonia Sensing Mask for Multifunctional Self-powered Monitoring Application - Jinzhu Huang; Yichen Huang; Ting Li; Haoming Xu; Hanguang Wu; Zhiqiang Su (Chemical Engineering Journal, 2025)

Dynamic changes in flavor characteristics of black tea during solid-state fermentation with Eurotium cristatum - Linyao Song; Fengwei Ma; Haijiang Chen; Qiang Fei; Guangcan Tao; Siyao Wu; Dajuan Shi; Junyi Deng; Degang Zhao; Xuan Dong; Yichen Zhao; Su Xu (Food Chemistry, 2025)

Spatio-temporally controlled all-in-one hydrogel microspheres for ulcerative colitis treatment based on cocktail strategy - Xiao Wang; Weijian Cheng; Xuebo Li; Di Wang; Lijun Su; Yanfen Cheng; Yichen Hu; Chen Zhang; Jinming Zhang (Chemical Engineering Journal, 2024)

Drift and afterburning effect on rocket exhaust plume impingement and optimization of deflector - Chengeng Zhao; Yifei Su; Zhongyi Sun; Yichen Wang; Guigao Le (Advances in Space Research, 2024)

Infrared Imageries of Human Body Activated by Tea Match the Hypothesis of Meridian System - Wenli Jin; Yichen Tao; Chen Wang; Lufei Wang; Xue Ao; Mingjie Su; Binwei Hu; Yuxiao Ouyang; Jiaxing Liu; Hui Li (Phenomics, 2023)

Role of Tim-3 in COVID-19: a potential biomarker and therapeutic target - Haodong Ma; Shengju Ren; Qingpeng Meng; Boyuan Su; Kun Wang; YiChen Liu; Junpeng Wang; Degang Ding; Xin Li (Archives of Virology, 2023)

The effects of co-culture on the expression of selected PKS genes in the lichenized fungus Xanthoparmelia taractica - Hongli Si; Yuemin Su; Yichen Wang; Tanay Bose; Runlei Chang (Mycological Progress, 2023)

Has green finance reform promoted green growth in Chinese industry? - Yichen Su; Zhonghua Cheng (Environmental Science and Pollution Research, 2023)

Revealing the synergistic mechanism of the generation, migration and nearby utilization of reactive oxygen species in FeOCl-MOF yolk-shell reactors - Shiyu Zuo; Yichen Ding; Li Wu; Fan Yang; Zeyu Guan; Su Ding; Dongsheng Xia; Xiaohu Li; Dongya Li (Water Research, 2023)

Effects of reduced pH and elevated pCO 2 on sperm motility and fertilisation success in blood clam, Tegillarca granosa - Wei Shi; Xinguo Zhao; Yu Han; Cheng Guo; Saixi Liu; Wenhao Su; Yichen Wang; Shanjie Zha; Xueliang Chai; Wandong Fu; Huicheng Yang; Guangxu Liu (New Zealand Journal of Marine and Freshwater Research, 2017)
Although it has been shown that ocean acidification generally has a negative impact on fertilisation success of broadcast spawning marine organisms, whether induced fertilisation success reduction is a consequence of elevated p CO 2 or decreased pH remains unclear. Therefore, the impacts of HCl‐ and CO 2 ‐induced acidified seawater on sperm motility and gametes fertilisation capability of a broadcast spawning bivalve species, Tegillarca granosa were investigated in the present study. The results showed that the fertilisation capability of both gametes was significantly reduced in either HCl‐ or CO 2 ‐acidified seawater. In addition, significant impacts on sperm motility were observed in the group exposed to CO 2 ‐acidified seawater, suggesting that this parameter is sensitive to p CO 2 instead of solely pH value. The differences between the two seawater acidification manipulating methods may be due to the intrinsic difference in diffusion capability of CO 2 and protons.